Family planning, antenatal and delivery care: cross‐sectional survey evidence on levels of coverage and inequalities by public and private sector in 57 low‐ and middle‐income countries. Issue 4 (7th March 2016) - Campbell, Oona M. R.; Benova, Lenka; MacLeod, David; Baggaley, Rebecca F.; Rodrigues, Laura C.; Hanson, Kara; Powell‐Jackson, Timothy; Penn‐Kekana, Loveday; Polonsky, Reen; Footman, Katharine; Vahanian, Alice; Pereira, Shreya K.; et al.
Abstract: Objective: The objective of this study was to assess the role of the private sector in low‐ and middle‐income countries (LMICs). We used Demographic and Health Surveys for 57 countries (2000–2013) to evaluate the private sector's share in providing three reproductive and maternal/newborn health services (family planning, antenatal and delivery care), in total and by socio‐economic position. Methods: We used data from 865 547 women aged 15–49, representing a total of 3 billion people. We defined 'met and unmet need for services' and 'use of appropriate service types' clearly and developed explicit classifications of source and sector of provision. Results: Across the four regions (sub‐Saharan Africa, Middle East/Europe, Asia and Latin America), unmet need ranged from 28% to 61% for family planning, 8% to 22% for ANC and 21% to 51% for delivery care. The private‐sector share among users of family planning services was 37–39% across regions (overall mean: 37%; median across countries: 41%). The private‐sector market share among users of ANC was 13–61% across regions (overall mean: 44%; median across countries: 15%). The private‐sector share among appropriate deliveries was 9–56% across regions (overall mean: 40%; median across countries: 14%). For all three healthcare services, women in the richest wealth quintile used private services more than the poorest. Wealth gaps in met need for services were smallest for family planning and largest for delivery care. Conclusions: The private sector serves substantial numbers of women in LMICs, particularly the richest. To achieve universal health coverage, including adequate quality care, it is imperative to understand this sector, starting with improved data collection on healthcare provision.